A bundled phosphate control intervention (4Ds) for adults with end‐stage kidney disease receiving haemodialysis: A cluster randomized controlled trial protocol. (12th July 2018) - Milazi, Molly; Douglas, Clint; Bonner, Ann
Abstract: Aim: To evaluate the effectiveness of a bundled self‐management intervention (Taking control of your phosphate with the 4Ds) to improve phosphate control among adults receiving haemodialysis. Background: Hyperphosphataemia occurs in end‐stage kidney disease and is associated with increased morbidity and mortality. While hyperphosphataemia can be managed through four methods (food, drinks, drugs and dialysis) adherence to these methods is challenging for patients. Studies also tend to focus on one method of phosphate control rather than bundling all methods together into a theoretically driven intervention. Design: A multisite cluster randomized controlled trial with repeated measures. Methods: Adults receiving haemodialysis with high serum phosphate levels (>1.6 millimoles per litre for at least 3 months) will be cluster randomized to standard care or intervention according to haemodialysis treatment shift. Informed by social cognitive theory, the intervention focuses on improving self‐efficacy and incorporates the "teach‐back" method of patient education. The intervention brings together essential phosphate control strategies of diet, drinks, drugs (phosphate binders) and dialysis prescription in a 12‐week self‐management education programme. The primary outcome is serum phosphate level. Secondary outcomes are knowledge of and adherence to phosphate control strategies and self‐efficacy for managing kidney disease. Discussion: Efforts to improve phosphate control have been undertaken although the optimal approach remains unclear. This study will make an important contribution to building an evidence base of phosphate control nursing intervention that can be delivered during routine haemodialysis. Trial registration: Australian and New Zealand Clinical Trials Registry Number ACTRN12617000703303 Abstract : 摘要: 目的: 旨在评估捆绑式自我管理干预措施的有效性(用4D控制您的磷酸盐水平), 以改善接受血液透析的成年人的磷酸盐控制情况。 背景: 高磷血症发生在肾病终末期, 并且与逐渐上升的发病率和死亡率有关。虽然可通过四种方法(食物、饮料、药物和透析)控制高磷血症, 但坚持使用这些方法对患者来说具有挑战性。许多研究也倾向于关注一种磷酸盐控制方法, 而不是将所有方法捆绑在一起, 形成以理论驱动的干预方案。 设计: 多位点集群随机对照试验采用了重复测量的设计。 方法: 将接受高血清磷酸盐水平血液透析(> 1.6毫摩尔/升, 至少接受透析3个月)的成人根据血液透析治疗班次随机集群分组至标准护理组或干预组。向干预组介绍社会认知理论, 干预组的重点是提高自我效能, 并结合患者教育的"教学"方法。该干预措施将饮食、饮料、药物(磷酸盐结合剂)和透析处方的基本磷酸盐控制策略合并到一个为期12周的自我管理教育计划中。主要关注的结果是血清磷酸盐水平, 其次是了解和遵守磷酸盐控制策略和管控肾脏疾病的自我效能。 探讨: 虽然目前我们仍不清楚最佳方法是什么, 但已采取措施改善磷酸盐的控制情况。本研究将有助于为磷酸盐管控护理干预措施提供重要依据, 此类护理干预措施可在常规血液透析期间实施。 试验注册: 澳大利亚和新西兰临床试验注册号ACTRN12617000703303: